What Do Place-Names Tell about non-Human Beings among Canadian Inuit? - Bordin, Guy (Journal of Northern Studies, 2018)
Typologies have been proposed to organise Inuit placenames in several categories based on the meaning of and glosses on the names. One possible category gathers those toponyms that are related to beings that are neither human nor animal (“other-than-animal non-human beings”). In Nunavut and Nunavik (Canadian Eastern Arctic), this category is used quantitatively to name an almost insignificant number of sites. On the other hand, however, such particular place-names are to be found all over the lands inhabited by Inuit, witnessing the “other” nature of this space by comparison to the space commonly frequented by people and animals.